Comparison of Civil Law and Common Law Legal Systems in the Application of Jurisprudence - Samudera Erlangga, Afga; Poespasari, Ellyne Dwi (Journal of Law, Politic and Humanities, 2024)
Civil law system (Continental European legal system) and Common law system (Anglo-Saxon legal system). Civil law system is a different legal system. The civil law system has a legal source that comes from the codification of written law or legislation, therefore judges are not bound by the principle of precedent or the doctrine of stare decicis, so that the law becomes the main legal reference, while the common law system has a history. The United Kingdom which makes court decisions as its legal basis when there is a case decided by a judge, the Judge's Decision is not only binding on the litigants but applies generally to similar cases. The common law system adheres to the principle of precedent or the doctrine of stare decicis (the obligation of judges to follow previous decisions in similar cases). In connection with the comparison of legal systems in Indonesia and in other countries in the application of Jurisprudence, there are two problem formulations, namely First, Comparison of law between civil law system and common law system. Second, the position of jurisprudence in the civil law system and the common law system.